Co-payment policies and breast and cervical cancer screening in Medicaid - Sabik, Lindsay M; Vichare, Anushree M; Dahman, Bassam; Bradley, Cathy J (The American journal of managed care, 2020)
This study investigated the relationship between state Medicaid co-payment policies and cancer screening for Medicaid-enrolled women. Cross-sectional analysis of administrative claims and enrollment data. Our data included Medicaid Analytic eXtract (MAX) outpatient claims files across 43 states in 2003, 2008, and 2010, the years for which both MAX data and state cost-sharing data were available. Data on enrollee demographics and screening services from enrollment and claims files were merged with state-year data on co-payment policies and county-level controls from the Area Health Resources File. Participants were nonelderly, nondisabled, nonpregnant women in the recommended age range for each screening service (50-64 years for mammograms; 21-64 years for Pap tests) enrolled in fee-for-service Medicaid. The main independent variable is whether an enrollee faced cost sharing for preventive services. We examined 3 categories of cost sharing: co-payments for all visits, including for preventive services; co-payments for outpatient visits but waived for preventive services; and no co-payments. The main outcome measure was receipt of mammogram or Pap test within a 12-month period. Medicaid enrollees with co-payments for preventive services were less likely to receive both screening mammograms and Pap tests than enrollees in states not requiring cost sharing for preventive services. Co-payments for preventive services discourage breast and cervical cancer screening among Medicaid enrollees. The effect is larger for breast cancer screening, which is costlier and requires an additional visit. Considering this evidence, cost sharing for preventive services may lead to adverse health consequences and greater long-term costs.